ACTIVITY OF SOLAR SCREEN FROM AVOCODO SKIN EXTRACT (PERSEA AMERICANA MILL.) IN VITRO - Muh. Amir Masruhim; Nurul Fitriani; Rahmatiyah Rahmatiyah (Faculty of Teacher Training and Education, Mulawarman University, 2022)
Sunscreen is a preparation that is used on the surface of the skin that works to absorb, scatter or reflect ultraviolet light. Therefore, it is necessary to use the ingredients to become active ingredients in sunscreen. The research objectives are to (a) To determine the total flavonoid content and total polyphenol content of avocado peel extract (Persea americana Mill.). (b) Knowing the sunscreen activity of avocado skin extract (Persea americana Mill.). This type of exploratory experimental research is based on a quantitative approach. The results showed that avocado skin extract (Persea americana Mill.) has a total flavonoid content of 10.855 mgQE/g extract and a total polyphenol content of 221.593 mgGAE/g extract. It is known that avocado peel extract (Persea americana Mill.) has sunscreen activity with an SPF value of 3.887 at a concentration of 500 ppm including minimal protection category. The results of the activity test showed that avocado skin sunscreen potential had phenolic comp